Correlations of Interleukin-6 (IL-6) ( G174C and G572C ) gene polymorphisms and sera levels with risk of Coronary Artery Disease in Thi – Qar province - Kadhem, Taqwa; Salih , Rasha (University of Thi-Qar Journal of Science, 2023)
The present study was carried out in the labs of Technical Institute –Al-Nasiriyah /Community Health Department and Nasiriyah Heart Center in Thi- Qar province, during the period of research was extended from January to July 2022 . The aim of study was to determination polymorphisms of IL-6 gene in patients with Coronary Artery Disease and measuring its levels in serum using a technique enzyme-linked immune sorbent adsorptive (ELISA). The study included a total of 100 Iraqi patients with coronary artery disease(CAD) and healthy control group their age between 3-85 years. DNA has been isolated and PCR was performed by using primers specific for genotypes of IL-6 gene (572 C/G and 174 C/G), the results showed that gel electrophoresis for amplified IL-6 gene of CAD patients, gel electrophoresis of 167bp (IL-6 572C/G) PCR products and 198bp PCR product(IL-6 174C/G). Frequency of genotypes for the IL6 gene showed a high frequency of GG genotype compared to the GC and CC genotypes in all study groups , the frequency of G and C allele in IL6 gene was 95 % and 5 %, respectively with significant differences between genotypes in various groups, in the patient group (90 %) had GC genotype, (10%) were heterozygote and had (0%) had CC genotype compare with control group, (100%) had GC genotype, (0%) were heterozygote and had (0%) had CC genotype. The immunological study showed that there was a significant increase of concentrations of (IL-6) in patients compared to the healthy control group. Thus it seems There is no correlation between IL-6 gene polymorphisms and the risk of coronary artery disease in Thi- Qar province and the Serological Assay (ELISA) showed a significant increase in the concentration of IL-6 in patients with coronary artery disease compared with the healthy control group.